'A Floating Population': The Niagara Corridor and Canadian/American Radicalism in the Nineteenth Century. (June 2015) - Redding, Art
<x content-type="archive" xml:space="preserve">Abstract</x> In both Canada and the US, Niagara Falls was famous from early on as a tourist and honeymoon destination. With the rapid settlement of the 'northwest' occasioned by the building of canals and railroads, the region also became a centre of commerce, transit, and industry in the years before the Civil War. The Niagara corridor held an important position on the Underground Railroad, as fugitive slaves moved up into Canada (and back). After the failed uprising of 1837, Canadian revolutionaries fled to safety in Rochester, Buffalo, and other cities south of the border. The 'burnt over' region of western New York spawned a variety of radical utopian communities and the first Women's Rights convention was held in Seneca Falls in 1848. Drawing on a variety of texts, testimonials, and documents, and taking a transnational approach, 'A Floating Population' contends that the Niagara region was a matrix of political radicalism as flows and exchanges of people, capital, and radical ideas through and across the border contributed to an unprecedented ferment of utopian, progressive, and radical forms of thought and social experimentation. The essay considers the uniquely radical republican culture situated in the border region of the Niagara corridor, a crossroads traversed by all manner of militant insurrectionists, radicals, abolitionists, feminists, journalists, fugitives, immigrants, homesteaders, itinerant labourers and tramps, Native Americans, mystics, and tourists.